East Armory at 75 East Newton Street, ca. 1960 - Unknown (Tufts Archival Research Center, 2005)
Elevated view east of the southwest elevation of the East Armory 75 East Newton Street, located between Albany Street to the southeast and Harrison Avenue to the northwest. Automobiles line the northeast side of Stoughton Street, which runs along the southwest elevation of the armory. Debris litters the area. 6 1/8 x 9 1/2, 8 x 9 15/16 overall Photographs